Snell's clinical neuroanatomy - Splittgerber, Ryan (Wolters Kluwer, 2018)
"This book contains the basic neuroanatomical facts necessary for the practice of medicine. It is suitable for medical students, dental students, nurses, and allied health students. Residents find this book useful during their rotations. The functional organization of the nervous system has been emphasized and indicates how injury and disease can result in neurologic deficits. The amount of factual information has been strictly limited to that which is clinically important"--Provided by publisher.